Influence Of Gender And Body Mass Index On Body Image Among Malaysian Adolescents Aged 11 To 15 Years - Phan, Ying Yih (2003)
This study was carried out to examine the influence of gender and body mass index on body image among adolescents aged 11 to 15 years in Malaysia. The adolescents were selected through a multi-stage random sampling involving random selection of secondary schools from rural and urban areas in Kedah and Pulau Pinang. The adolescents were categorized as underweight, normal weight and overweight based on their body mass index (8MI). Out of 2050 adolescents w ho completed the body image questionnaires, 769 adolescents were selected to complete a 3-day dietary record and a 3-day physical activity record . Out of the 769 respondents, 52.9% were female and 47. 1 % male. This study found that the majority of the adolescents were concerned with body shapes, selecting health as their reason for concern. Females however were more likely to choose beauty for their concern and look to models and idols